Educators’ perspective on parental involvement in homework at a rural primary school in Palala - Hlongolane A. Seleka; Charles S. Masoabi (South African Journal of Childhood Education)
Background: Educators have a very important job of moulding learners’ lives. However, they cannot do it alone, they need assistance from parents. Every child is different and learns differently and most of the information a child receives comes from their parents.